2002
DOI: 10.1007/bf03192335
|View full text |Cite
|
Sign up to set email alerts
|

Absolute bioavailability of [14C] genistein in the rat; plasma pharmacokinetics of parent compound, genistein glucuronide and total radioactivity

Abstract: The systemic plasma pharmacokinetics of genistein were determined in rats to evaluate the absolute oral bioavailability and make comparison with similar data in the literature derived from humans subjects. The plasma concentrations of genistein, genistein glucuronide and carbon-14 were determined by LC-MS/MS and liquid scintillation counting following oral and intravenous dosing with [14C]genistein (4 mg kg(-1) body weight). The absorption of total radioactivity from the gut, (parent compound and metabolites),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 30 publications
3
59
1
Order By: Relevance
“…The authors of a study investigating the absolute bioavailability of genistein in rats noticed a marked sex difference with regard to bioavailability of this isoflavone. After oral administration of 15 µmol genistein/kg BW, bioavailability of the unchanged isoflavone was 6.8% in male and 14.6% in female rats [46].…”
Section: Absorption and Bioavailability Of Flavo-noidsmentioning
confidence: 97%
“…The authors of a study investigating the absolute bioavailability of genistein in rats noticed a marked sex difference with regard to bioavailability of this isoflavone. After oral administration of 15 µmol genistein/kg BW, bioavailability of the unchanged isoflavone was 6.8% in male and 14.6% in female rats [46].…”
Section: Absorption and Bioavailability Of Flavo-noidsmentioning
confidence: 97%
“…However, an ϳ10-fold increase in exposure levels of genistein conjugates did not appear to correlate with a slight increase in aglycone (Ͻ2-fold compared with that in WT mice) in Bcrp1 knockout mice. More importantly, numerous previous studies showed that genistein is a highly permeable compound and has good oral absorption (Ͼ50%) in vivo (Coldham and Sauer, 2000;Coldham et al, 2002;Chen et al, 2005a;Zhou et al, 2008). Impaired BCRPmediated efflux of genistein aglycone cannot explain the ϳ6-fold increase of oral bioavailability of total genistein in Bcrp1 knockout mice, because the efflux ratio of genistein in a pair of BCRP/Bcrpoverexpressed cell lines were less than 2.5.…”
Section: Introductionmentioning
confidence: 96%
“…Genistein, a plant phenolic and one of the most commonly consumed phytoestrogens, has been extensively studied because of its pharmacological and beneficial effects (Banerjee et al, 2008;Yang et al, 2012), however, with the realization that the full biological potential of genistein (i.e., aglycone) is severely hampered by its extensive metabolism into glucuronide and sulfate conjugates in humans after oral administration (Shelnutt et al, 2000;Coldham et al, 2002;Gu et al, 2006;Hosoda et al, 2010). On the other hand, although generally less active than the aglycone, genistein glucuronides retain the ability to prevent lipid oxidation and possess modest activity to enhance human natural killer cells at nutritionally relevant concentrations (Zhang et al, 1999b;Kgomotso et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, several clinical trials are ongoing to test the anticancer efficacy of soy isoflavones and green tea, both of which contain flavonoids as the active ingredients (Crowell, 2005). A major impediment to the development of flavonoids is their poor bioavailabilities, which are usually approximately 3 to 5% (Coldham et al, 2002). Poor bioavailabilities make it more difficult to test flavonoids in a clinical setting because it requires a large number of subjects because exposure levels are going to be highly variable across the population.…”
mentioning
confidence: 99%